Dampak Negatif Pernikahan Dini Terhadap Kualitas Hidup Perspektif Maqhasid Syariah dan Undang-Undang Pernikahan Nomor 16 Tahun 2019 - Muhammad Ali Masykur; Hari Widiyanto; Arifuat Marzuki (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Early marriage remains a prevalent phenomenon in Indonesia, with a profound impact on the quality of individuals’ lives. From the perspective of Maqāṣid al-Syarī‘ah, marriage is considered a completion of worship aimed at achieving human welfare. Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 on Marriage stipulates the minimum age for marriage for both men and women as 19 years old. This provision aims to prevent and minimize various negative consequences arising from the practice of early marriage. This study aims to analyze the essence of early marriage from the perspective of Law Number 16 of 2019 and Maqāṣid al-Syarī‘ah, identify the factors contributing to the high prevalence of early marriage, and examine its impacts on individuals’ quality of life.This research employs a qualitative method with a library research approach, enabling the researcher to gain an in-depth understanding of early marriage from the perspectives of Maqāṣid al-Syarī‘ah and the Compilation of Islamic Law, as well as its implications for individuals’ lives. The findings reveal that early marriage has negative impacts on various aspects of life, including family economic instability, low income levels, increased risks of poverty, divorce, and even neglect. Limited financial resources also lead to difficulties in accessing healthcare services, which consequently affects the overall quality of family health.